Guardian Spirits, Omens and Meat for the Clans: The Place of Animals among the Apatanis of Arunachal Pradesh - Chaudhuri, Sarit K. (Religions of South Asia, 2013)
Animals play significant roles in the construction of the cultural and religious life of the Tani indigenous communities (e.g. Adis, Nyishis, Galos, Apatanis and Tagins) of Arunachal Pradesh. Without the ritual sacrifice of mithuns (forest buffalo), hardly any agricultural festival takes place. Similarly, exchange of mithuns during marriage is mandatory among most of the Tani tribes. Ritual sacrifices of pigs are common when shamans and oracles must negotiate with the world of spirits. This article discusses animal sacrifice amongst the Apatanis, with particular emphasis on the myoko and murung festivals. On such occasions, animal sacrifice and rites involving hepatoscopy are performed to main a balance between the different worlds. Local shamans, the holder of territorial and ancestral knowledge, explain through oral narratives how the creation of the world (and thus the existence itself of the tribe) depends on specific non-human animals. Ritualized mythical narrations also provide a rationale behind such extensive sacrificial performances. This article is an attempt to report, preserve and reflect on a still unexplored aspect of South Asian culture, and to underscore the significance of non-human animals in the multifarious construction of cultural and religious life in the folklore tradition of Tani indigenous tribes ofArunachal Pradesh.